Підводно-археологічні роботи біля скель Адалар у Криму в 2009 р. - Вахонєєв, В.В. (Археологічні дослідження в Україні, 2010)
In 2009, underwater archaeological research around the Adalars revealed the material of various chronological periods of Ancient and Mediaeval times. The results showed the perspectiveness of underwater research in this area.